Indonesian Women’s Struggle for Equality in Church and Society - Theis, Julia (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
According to ancestral custom, the position of Indonesian women isequal to the men. Indonesian women have marriage’s right equal to men.The influence of Islam, among other things, caused the position of Indonesianwomen to be inferior to the men. Indonesian women were struggling forequality in the society. Although, women have a special position in thechurch because of their roles in the early history of Christianity, women haveto struggle for equality leadership roles in church. It was caused by the fallenhuman nature and the wrong interpretation of the Bible. The purpose of thispaper is to describe the struggle of Indonesian women for equality in churchand society, and to find Pentecostal theology solutions which can help themin their struggle for equality. In order to accomplish this purpose, I willdiscuss the cultural, economic and political perspective on Indonesianwomen. I also will discuss position of women in Indonesian churchconcerning their roles in the church.